Study on clinical, histopathological and dermoscopic features of palmoplantar pustulosis and palmoplantar psoriasis with pustules - George, Neethu M.; Sangolli, Prabhakar M.; Thomas, Rosamma; John, Jerry R. (International Journal of Research in Dermatology, 2024)
Background: Palmo-plantar pustulosis (PPP) and palmoplantar psoriasis with pustules (PPso)/Palmoplantar pustular psoriasis are entities that present with chronic cyclical eruptions of vesicles and pustules of palms and soles, which were initially considered to be similar but was defined as separate entities by the international psoriasis council in 2007. Individuals with PPP are at increased risk of psoriasis vulgaris, psoriatic arthritis, autoimmune thyroid disease and 90% of pustulosis patients can have psoriasis-like rash at some stage of the disease. Aim was to assess the clinical, histopathological and dermoscopic features of PPP and palmoplantar psoriasis with pustules. Methods: A cross sectional analysis of all patients who presented to us over 1 year with vesicles and/or pustules of hands and/or feet and were diagnosed with PPP and palmoplantar psoriasis with pustules/palmoplantar pustular psoriasis, both clinically and histologically, were done. The severity was analysed using palmoplantar pustulosis area severity index (PPPASI) and the clinical, histological and dermoscopic features were noted. Results: Twenty-four patients were categorized into 2 groups of 12 each, with a male predominance in both the groups. Majority (66.6%) of PPP belonged to the age group of 20-40 years whereas 83% of PPso belonged to >40 years of age. Dermoscopic findings noted in both groups were translucent yellow areas, yellow/red-brown globules, dotted regularly arranged vessels, yellow crust and globules following dermatoglyphics. Conclusions: The study, though with limited sample size, highlights few clinical, histopathological and dermoscopic features which helps in differentiating the two groups.